2009
DOI: 10.1371/journal.pmed.1000198
|View full text |Cite
|
Sign up to set email alerts
|

The Global Spread of Hepatitis C Virus 1a and 1b: A Phylodynamic and Phylogeographic Analysis

Abstract: Using phylodynamic and phylogeographic methods, Angelos Hatzakis and colleagues find that the global spread of Hepatitis C virus coincided with widespread use of transfused blood and with the expansion of intravenous drug use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

22
168
1
15

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 191 publications
(216 citation statements)
references
References 54 publications
22
168
1
15
Order By: Relevance
“…Previous studies have estimated the tMRCA for subtype 1a in other parts of the world, using limited segments of the genome. For instance, a previous global evolutionary analysis of subtype 1a, using the NS5B region of sequences obtained from 21 countries, placed the tMRCA at a similar time point and with a Bayesian skyline plot showing a similar pattern to that reported here for North America [1]. However, this study included a disproportionate number of North American sequences (399 vs 443 sequences from 20 other countries combined).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Previous studies have estimated the tMRCA for subtype 1a in other parts of the world, using limited segments of the genome. For instance, a previous global evolutionary analysis of subtype 1a, using the NS5B region of sequences obtained from 21 countries, placed the tMRCA at a similar time point and with a Bayesian skyline plot showing a similar pattern to that reported here for North America [1]. However, this study included a disproportionate number of North American sequences (399 vs 443 sequences from 20 other countries combined).…”
Section: Discussionsupporting
confidence: 59%
“…Hepatitis C is a chronic viral infection predominantly spread via blood-to-blood contamination during injecting drug use, with outbreaks also attributed to nonsterile medical practices, unscreened blood transfusions and sexual transmission among men who have sex with men [1][2][3][4][5]. The hepatitis C virus (HCV) genera are divided into 7 genotypes and 67 subtypes [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the present analysis provides tighter CIs than those reported previously for subtype 1b using two subgenomic regions (1905-1965 and 1806-1959; [12]), reflecting the increased information gained from using whole-genome reference sequences and from the inclusion of the two 1953 sequences. While direct amplification of viral genomes from archived biological samples may prove challenging using long-range PCR approaches, owing to nucleic acid degradation, modern high-throughput sequencing technologies may alleviate such difficulties, as they have done in the field of ancient DNA research [31].…”
Section: Discussioncontrasting
confidence: 49%
“…Phylogenetic analyses have suggested that the direction of spread was mainly from developed countries to the developing world, with the USA as a likely source location [12]. It is hypothesized that the global dispersal of subtypes 1a and 1b occurred in two steps, starting with widespread export of the virus from the USA to the rest of the world around 1940-1950, followed by local expansion of the exported lineages [12]. The initial step coincided with the international transportation of dried plasma units, a massive operation that involved the pooling and shipping of at least 10 million independent donations to sites of military operations over 5-10 years [13].…”
Section: Discussionmentioning
confidence: 99%